Community health worker roles and their evolving interprofessional relationships in the United States. Issue 4 (4th July 2022) - Washburn, David J.; Callaghan, Timothy; Schmit, Cason; Thompson, Emily; Martinez, Denise; Lafleur, Megan
ABSTRACT: In the United States, growing attention to the cost of care, the social determinants of health, prevention, and population health, signals a refocusing of efforts on value-based care. Just as Accountable Care Organizations and alternative payment models exemplify this shift in attention, so does the increasing integration of Community Health Workers (CHWs) into the US health care system. CHWs are often referred to as "bridge figures, " helping clients to navigate what are oftentimes complicated pathways to access a variety of needed services. The integration of CHWs into interprofessional care teams is a process that takes time, and can lead to conflict as traditional care models are disrupted. Through focus groups with CHWs in rural and urban areas of four states, this work identifies and describes three early stages in the evolving interprofessional relationships between CHWs and other care providers. These stages are characterized by: (1) a lack of knowledge and understanding of CHW roles, (2) conflict and competition, and (3) engagement and integration of CHWs into patient care teams. A better understanding of the evolving process of CHW integration is critical to facilitate education and training that will more quickly encourage the development and efficacy of modern models of interprofessional care that include CHWs.